Effect of crossbreeding on some productive characteristics of laying hens - Tawfeq, Esraa Mobsher; Sabeeh, Haytham Mohammed; Al-Kurjia, Omar AbdulHameed (Journal of agricultural, environmental and veterinary sciences, 2023)
5The hybridization process is considered One of the crucial techniques in programs aimed at enhancing and refining animal breeds, as it works on increasing production and transferring and collection of a large number of desirable genes present in the resulting hybrids, thereby improving them. The generation of chickens resulting from the hybridization of breeds Generally excels in various economic aspects like growth rate, feed efficiency, age of initial egg laying, egg output, and meat production, and meat production. To improve the local chickens, which have a rich reservoir of genes and traits that have given them the ability to adapt to local environmental conditions and resistance to diseases, the production performance is still low. Therefore, this study aims to emphasize the significance of crossbreeding local chickens with high-yield breeds while preserving their unique traits. This approach holds great promise for enhancing the productivity of layer chickens.